2020
DOI: 10.25259/sni_550_2019
|View full text |Cite
|
Sign up to set email alerts
|

Burr hole drainage without irrigation for chronic subdural hematoma

Abstract: Background: Chronic subdural hematoma (CSDH) is one of the most common neurosurgical conditions, with different strategies for treatment. Most recent trials favor the use of drainage to reduce the recurrence rate. However, few reports have discussed the efficacy of burr hole drainage without irrigation for treating CSDH. This study aimed to examine the efficacy of burr hole drainage without irrigation in a series of 385 symptomatic CSDH lesions. Methods: This retrospective study included a series of 385 sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
2
5
0
1
Order By: Relevance
“…As in the study by Huang et al, there was no correlation in our cohort between PV and neurological outcome of patients (11). Uda et al confi rmed the effect of PHV on the recurrence rate of NASH, which is in line with our study (16). Molina et al reported that PHV > 80 ml is signifi cantly more frequent in the hematoma recurrence group of patients after evacuation (17).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As in the study by Huang et al, there was no correlation in our cohort between PV and neurological outcome of patients (11). Uda et al confi rmed the effect of PHV on the recurrence rate of NASH, which is in line with our study (16). Molina et al reported that PHV > 80 ml is signifi cantly more frequent in the hematoma recurrence group of patients after evacuation (17).…”
Section: Discussionsupporting
confidence: 89%
“…It should be noted that in our study group of bilateral hematomas, no homogeneous hyperdense morphological type of hematoma occurred. Other various factors are referred to as conditions carrying the risk of hematoma recurrence and worse neurological outcome, namely arterial hypertension, absence of postoperative drainage, early removal of drainage tube, hematoma evacuation via burr holes, antithrombotic agents, midline shift, admixture of acute blood in post-evacuation hematoma cavity, phatic disorder, preoperative seizures, disorder of consciousness, thrombocytopenia, diabetes mellitus, brain atrophy, non-hyperintensity on T1-weighted magnetic resonance, general anesthesia and heterogeneous density of hematoma (6,7,10,12,(16)(17)(18)(20)(21)(22)(23). Further studies focusing on the results of surgical treatment of bilateral NASH are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, bone flap craniotomy was more commonly performed in the subacute type of the extended classification and this treatment might have contributed to the low observed recurrence rate observed. Finally, other treatment algorithms, such as burr hole drainage without irrigation [ 28 ] or placement of subperiostal drains [ 29 ], were not assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[50,145,164] Si bien la irrigación permite una rápida y efectiva evacuación del HSDC, no hay evidencia que demuestre que la irrigación es superior a no realizarla y podría agregar otros riesgos. [50,66,97,137,145,151,164] El tipo de solución para irrigar también ha sido estudiado. Un trabajo encontró que el uso de LCR artificial (solución de composición similar al LCR) tuvo un efecto benéfico comparado con la irrigación con solución salina normal.…”
Section: Controversias De La Cirugíaunclassified